A new perspective on social sustainability: examining Amazon workers’ working conditions and protests applying computational methods in social sciences - Ali Çelik; Naim Göktaş; Engincan Yıldız (Discover Sustainability)
Abstract The regulation of workers' working conditions is a crucial issue for achieving social sustainability. This research aims to investigate the reactions to the workers' protests at Amazon, one of the world's largest companies, in the context of the gig economy. The originality of the study lies in the analysis of 5500 comments from the YouTube channel on the subject in terms of social sustainability applying the computational methods in social sciences (CMSS). The analysis revealed some remarkable findings. For example, it was found that the working conditions of Amazon workers contravene the International Labour Organization (ILO) and the United Nations (UN) definition of decent work. It also found that the zero-hours contract, which is characteristic of the gig economy, and the negative externalities it creates, as well as extremely low wages, were among the most significant objections. These findings are crucial for governments, international institutions and policymakers who are committed to social sustainability. It should be noted that it will be impossible to achieve social sustainability without raising labour standards. In particular, governments and institutions need to develop policies that are in favour of workers.